2002
DOI: 10.1080/13561820220146694
|View full text |Cite
|
Sign up to set email alerts
|

Supervision: the process of life-long learning in social and educational professions

Abstract: The supervision process represents one of the possible processes of life-long learning and development of an adult. This paper presents a developmental-educational model of supervision. It is a specific learning developmental and supportive method of professional reflection and counselling used in social and educational settings in Slovenia. Different concepts that explain learning and acquiring competence in the process of supervision are discussed. Special emphasis is given to the process of experiential lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 10 publications
2
20
0
Order By: Relevance
“…Although there appears to be a consensus on the existence and importance of the deskillingdevelopment pattern in professional development (see for example Zorga, 2002), there also appears to be surprisingly little empirical support for it. To illustrate, James, Blackburn, Milne and Reichelt (2001) assessed the development of competence amongst a multi-disciplinary group of 20 professionals (attending a post-graduate certificate training programme in CBT) with the revised Cognitive Therapy Scale (CTS-R).…”
Section: Illustration 2: the Deskilling-development Patternmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there appears to be a consensus on the existence and importance of the deskillingdevelopment pattern in professional development (see for example Zorga, 2002), there also appears to be surprisingly little empirical support for it. To illustrate, James, Blackburn, Milne and Reichelt (2001) assessed the development of competence amongst a multi-disciplinary group of 20 professionals (attending a post-graduate certificate training programme in CBT) with the revised Cognitive Therapy Scale (CTS-R).…”
Section: Illustration 2: the Deskilling-development Patternmentioning
confidence: 99%
“…through rote learning, as in memorising parts of the knowledge-base that underpins competence), development that requires "deeper" learning is typically associated with some personal discomfort (e.g. feeling inadequate: Dewar and Walker, 1999) and deskilling (feeling confused, helpless and incompetent: Zorga, 2002). Nel (2006) regards this pattern as well-documented in the training of counsellors and psychotherapists, citing reviews by developmental theorists (including Friedman and Kaslow, 1986;Skovholt and Ronnestad, 1992).…”
Section: Illustration 2: the Deskilling-development Patternmentioning
confidence: 99%
See 1 more Smart Citation
“…It found that explicit use of the theory was limited but with some notable exceptions: Although not situated within the confines of IPE delivery in a HEI, Zorga (2002) published a developmental-educational model of professional supervision in practice. In this model, the supervisor mediates the learner's reflection on a relevant work issue from which they wish to learn ⁄ develop.…”
Section: Social Constructivismmentioning
confidence: 99%
“…In 2002, stigma and discrimination were addressed in an article about supervision in mental health (53).…”
Section: Reports On Education Against Stigmamentioning
confidence: 99%